Strengthening Student Character through the Pancasila Student Profile Strengthening Project at Nahdlatul Ulama Elementary School - Salam, Salam; Sakinah, Nurul; Ahmad, Ahmad Shamsuddin bin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2025)
The Pancasila Student Profile Strengthening Project (P5) integrates Pancasila values ​​into project-based learning. This study aims to describe the implementation of P5 at the Nahdlatul Ulama Elementary School (MINU) and identify the challenges and opportunities faced. This study applies a descriptive qualitative approach, with data obtained through observation, interviews, and documentation. The results of this study found that the implementation of P5 was carried out in stages by adjusting to the readiness and available resources for two main themes, local wisdom and sustainable lifestyles. The implementation followed three phases: planning, implementation, and project culmination. Challenges faced in implementing P5 include a lack of teacher understanding, student conditions, variations in parental support, and difficulties in evaluating project results. This study recommends improving teacher competency training, strengthening collaboration with parents and the community, and developing more holistic evaluation methods to implement P5.